2019
DOI: 10.1002/cam4.2762
|View full text |Cite
|
Sign up to set email alerts
|

The extent of lymph node yield in central neck dissection can be affected by preoperative and intraoperative assessment and alter the prognosis of papillary thyroid carcinoma

Abstract: Background: Lymph node yield (LNY) was implemented in the stratification of papillary thyroid cancer (PTC) patients. The effect of LNY may be related to the extent of surgery. This study aims to identify influencing factors for LNY in central compartment neck dissection (CND). Methods: Data of 13 712 consecutive PTC patients were analyzed retrospectively.Risk factors for LNY in CND and distribution characteristics of LNY were evaluated. Its relationship with prognosis was studied in another cohort of 136 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…We therefore further evaluated the predictive factors for the lateral multiple-metastasis in N1b PTMC. Other studies (4,14,28) have reported that CPLN was a predictor of lateral LNM in PTC patients. Xiao et al (29) conducted ipsilateral LND for PTC patients and demonstrated that CPLN ≥ 2 was a reliable indicator of lateral LNM.…”
Section: Discussionmentioning
confidence: 88%
“…We therefore further evaluated the predictive factors for the lateral multiple-metastasis in N1b PTMC. Other studies (4,14,28) have reported that CPLN was a predictor of lateral LNM in PTC patients. Xiao et al (29) conducted ipsilateral LND for PTC patients and demonstrated that CPLN ≥ 2 was a reliable indicator of lateral LNM.…”
Section: Discussionmentioning
confidence: 88%
“…Generally, PTC has an excellent prognosis, but neck lymph node metastases (LNM) are quite common, which increases the risk of tumor relapse and reduce long-term survival (2)(3)(4). Evaluating LNM accurately is thus essential for appropriate initial surgical management (5,6). The Delphian lymph node (DLN) (prelaryngeal lymph node) was named by the "Oracle of Delphi" (7), the most famous religious prophet in the temple of Apollo of ancient Greek times.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid surgery is known to encompass a broad range from benign causes to malignant causes, which can vary from limited thyroidectomy to central or lateral LN dissection. A previous study reported that the incidence of nerve damage seen could show a difference depending on the extent of the surgery [ 3 ]. Although nerve damage can develop associated with traction or thermal causes, it has been reported that in patients where neck dissection is performed, there is a higher risk associated with invasion of metastatic LNs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The basic treatment of PTC where there is LNM is full resection of the primary tumor and regional LNM [ 2 ]. Depending on the level of lymphatic spread, central or modified radical lymph node dissection (MLND) are the treatment options used in surgery [ 3 ].…”
Section: Introductionmentioning
confidence: 99%